Biochemical and Histopathological Assessment of Some Organs in Rats Administered Picralima Nitida Aqueous Fruit-Pulp Extract - Ilenowa Julius Owie; Eboigbe Mckay Ikponwosa; Obasuyi Faith; Adesoye Success; Ebizugbe Oghosa Enoch; Osagiede Christian Eghosa; Imarenakhue Uhunoma; Osayande Paul Osayowanbor; Innocent Nosakhare Flourish; Ajayi Osagioduwa Joseph; Fidelis E. Olumese; Oboh Henrietta. A (Research Synergy Foundation, 2024)
Picralima nitida (Apocynaceae) is frequently used in ethnomedicine to manage various illnesses. The potential and safety of P. nitida aqueous, unripe fruit-pulp extract were assessed. Unripe P. nitida fruit pulp was cleaned, dried to a persistent mass, and crushed to powder. Then, it was immersed in distilled water for 72 h, filtered, and freeze-dried. The study involved six groups of rats, each with an average weight of 160–185 g, who were given 200–3000 mg/kg of pulp's aqueous extract daily for 35 days, with weekly measurements of weight, fasting blood glucose levels, and feed intake. Blood samples were obtained for biochemical tests, and certain organs underwent histopathological examination. A considerable (P > 0.05) increase in body weight was accompanied by a significant (P > 0.05) decrease in blood glucose and cholesterol levels. The relative organ weights did not differ significantly at a significance level of P > 0.05. ALT increased as doses of the extract rose. Serum electrolytes were altered at higher extract concentrations. The urea and creatinine concentrations were not appreciably changed. The hematological assessment revealed no variations in the quantity of leukocytes (total and differential), but there was a significant increase in hemoglobin at low doses. Histopathological studies revealed heart myocarditis, kidney tubular necrosis, liver hepatitis, pancreatitis, and bronchiolar mucosa ulceration in unripe P. nitida fruit pulp extract at a dosage of 3000 mg/kg body weight. The findings revealed that unripe P. nitida fruit pulp extract is relatively safe at low concentrations.